Automatic Event Integrated System Based on User Profile - Bisen, N; Banerjee, P (International Journal of Computer Sciences and Engineering, 2025)
Event Integrated System is a platform where students can post events and workshops of their colleges as like they post news feed in other social media platforms. With the help of this system, students of different colleges will be aware of different college activities that are happening in their locality. The major advantage of this web portal is that we do not have to spend time on promotion of events. All the hectic work related to promotion of particular events is performed online. Many a times, we see that there are clash of events of different colleges on the same date. With the help of this system, this problem can be eliminated up to a higher extent and this will increase the overall participation in a particular event of a college. The technology that is used to build this system is Node.js and the database used is MongoDB.